Early And Recent Development Of Reconstructive Microsurgery Subspeciality In Dr. Cipto Mangunkusumo National Hospital, Universitas Indonesia (1983-2020) - Ramadan, Mohamad Rachadian; Ralena, Nadhira Anindita; Triatmoko, Sara Ester; Atmodiwirjo, Parintosa (Jurnal Plastik Rekonstruksi, 2019)
Plastic surgery in Indonesia was pioneered and developed by Moenadjat Wiratmadja, MD., in 1958. This specialty experienced many developments and improvements over time with more specific subspecialties to facilitate the advancement of the science of plastic surgery, including the reconstructive microsurgery subspecialty. The reconstructive microsurgery service in the plastic surgery division dr. Ciptomangunkusumo National Hospital (RSCM), Jakarta, Indonesia was first initiated by Sidik Setiamiharja, MD., self-taught from the textbooks. In late 1985, following the success of conducting the first basic microsurgery course in Jakarta, the plastic surgery team in RSCM which consisted of Sidik Setiamihardja, MD, Chaula L. Sukasah, MD and Gentur Sudjatmiko, M.D. pioneered many of the first microsurgery cases, including the first major limb replantation, first penile replantation and the first free flap. Overtime, the reconstructive microsurgery subspecialty has been growing significantly. In 2019, the number of free flap cases at RSCM reached the highest number in Indonesia with 90 free flap cases with 94% success rate.